Poder de mercado em mercados elétricos desregulamentados com integração de fontes de energia renováveis - RODRIGUEZ, Yenny Suhail Guerra (2020)
Market power is an effect that exists in electricity markets and is defined as the ability of a market participant to profitably maintain prices above a competitive level for a significant period of time. This fact generally stems from factors that may be the intention of some companies to dominate the market, or also due to the existence of transmission or congestion restrictions that lead some companies to exercise local market power. Market power is not desirable, as it is a symptom of a non-competitive sector that can generate actions detrimental to the functioning of the market. With the reform of the electricity sector, in deregulated electricity markets, market participants can trade electricity transparently and pay or receive funds for the electricity supplied, but study market power, where certain market problems arise such as the existence of barriers to entry for new generators, they make the exercise of market power and its detection extremely challenging. Techniques have been proposed to identify and detect the exercise of market power, through the study of the structure of the markets and the behavior of its participants in the operations of production and commercialization of electric energy. In addition, the world's electricity markets face resource adequacy challenges, with the passage of profound transformations and migration to new forms of energy generation that imply important changes in the structure of electricity production costs, especially when a relevant part the provision is provided by renewable sources, such as wind that impacts the operation of the network due to its intermittency and unpredictability, and is one of the technologies with the greatest presence to date in the electricity markets. The objective of this work is to carry out a study on the possible exercise of market power in electric markets, considering the influence of the inclusion of sources of wind generation.